Laboratory diagnosis of paraneoplastic pemphigus. (31st October 2013) - Poot, A.M.; Diercks, G.F.H.; Kramer, D.; Schepens, I.; Klunder, G.; Hashimoto, T.; Borradori, L.; Jonkman, M.F.; Pas, H.H.
Summary: Background: Paraneoplastic pemphigus (PNP) is a multiorgan disease characterized by antibodies against plakins, desmogleins and the α2‐macroglobulin‐like‐1 (A2ML1) protein, in association with an underlying neoplasm. Accurate diagnosis relies on the demonstration of these autoantibodies in serum. Objectives: To evaluate the value of different laboratory techniques in the serological diagnosis of PNP. Methods: We performed immunoblotting, envoplakin (EP) enzyme‐linked immunosorbent assay (ELISA), indirect immunofluorescence (IIF) on rat bladder, radioactive immunoprecipitation and a nonradioactive combined immunoprecipitation‐immunoblot assay. Additional assays included BP180 ELISA and BP230 ELISA. We included the sera of 19 patients with PNP and 40 control subjects. Results: The sensitivities were 63% for anti‐EP ELISA, 74% for rat bladder IIF, 89% for immunoblotting, 95% for radioactive immunoprecipitation and 100% for nonradioactive immunoprecipitation. Specificities ranged from 86% to 100%. The BP180 and BP230 ELISAs had low sensitivity and specificity for PNP. The combination of rat bladder IIF and immunoblot showed 100% sensitivity and specificity. The analysis of sequential PNP sera showed that antibody titres may decrease over time, possibly resulting in negative outcomes for EP ELISA and rat bladder IIF studies. Conclusions: The detection of autoantibodies against EP and periplakin, or A2ML1 by immunoprecipitation is most sensitive for PNP. The combination of rat bladder IIF and immunoblotting is equally sensitive and highly specific, and represents an alternative valuable and relatively easy approach for the serological diagnosis of PNP. Abstract : What's already known about this topic? Paraneoplastic pemphigus (PNP) is a severe autoimmune disease characterized by anti plakin and anti‐α2 macroglobulin‐like 1 (A2ML1) autoantibodies. Its laboratory diagnosis is based on demonstrating the presence of these autoantibodies in serum. What does this study add? This study shows the diagnostic value of an array of laboratory techniques for PNP. We confirm that immunoprecipitation studies are the most sensitive, partly because of the detection of anti‐A2ML1 antibodies. Rat bladder indirect immunofluorescence in combination with immunoblotting provides an easier and accurate alternative to immunoprecipitation. Envoplakin ELISA is of lower sensitivity.